Genetic characterization of Brazilian annual Arachis species from sections Arachis and Heteranthae using RAPD markers - Creste, S.; Tsai, S. M.; Valls, JFM; Gimenes, M. A.; Lopes, C. R. (Springer, 2005)
The genus Arachis is divided into nine taxonomic sections. Section Arachis is composed of annual and perennial species, while section Heteranthae has only annual species. The objective of this study was to investigate the genetic relationships among 15 Brazilian annual accessions from Arachis and Heteranthae using RAPD markers. Twenty-seven primers were tested, of which nine produced unique fingerprintings for all the accessions studied. A total of 88 polymorphic fragments were scored and the number of fragments per primer varied from 6 to 17 with a mean of 9.8. Two specific markers were identified for species with 2n = 18 chromosomes. The phenogram derived from the RAPD data corroborated the morphological classification. The bootstrap analysis divided the genotypes into two significant clusters. The first cluster contained all the section Arachis species, and the accessions within it were grouped based upon the presence or absence of the 'A' pair and the number of chromosomes. The second cluster grouped all accessions belonging to section Heteranthae.
Keywords: Arachis; genetic similarity; germplasm; peanut; RAPD markers